Neural responses to emotional faces in women recovered from anorexia nervosa - Cowdrey, F; Harmer, C; Park, R; Mccabe, C (2012)
Impairments in emotional processing have been associated with anorexia nervosa. However, it is unknown whether neural and behavioural differences in the processing of emotional stimuli persist following recovery. The aim of this study was to investigate the neural processing of emotional faces in individuals recovered from anorexia nervosa compared with healthy controls. Thirty-two participants (16 recovered anorexia nervosa, 16 healthy controls) underwent a functional magnetic resonance imaging (fMRI) scan. Participants viewed fearful and happy emotional faces and indicated the gender of the face presented. Whole brain analysis revealed no significant differences between the groups to the contrasts of fear versus happy and vice versa. Region of interest analysis demonstrated no significant differences in the neural response to happy or fearful stimuli between the groups in the amygdala or fusiform gyrus. These results suggest that processing of emotional faces may not be aberrant after recovery from anorexia nervosa. © 2012 Elsevier Ireland Ltd.